The story of the missing canine - Fernandes, Shoba (BMJ Publishing Group, 2011)
Odontomas are usually associated with permanent teeth and rarely with primary dentition. The consequences of their presence are several clinical complications. Presented here is a case where diagnosis and management of an odontome causing impaction of primary tooth is discussed thus emphasising need for alertness in a clinician using the aid of radiological examination for early detection and subsequent intervention.